Effects of Clostridium butyricum Capsules Combined with Rosuvastatin on Intestinal Flora, Lipid Metabolism, Liver Function and Inflammation in NAFLD Patients: Effects of Clostridium butyricumand Rosuvastatinin NAFLD - Zhu, Wenjie; Yan, Meizhu; Cao, Haibin; Zhou, Jun; Xu, Zhongqing (Cellular and Molecular Biology, 2022)
The objective of this study was to investigate the effects of Clostridium butyricum capsules combined with rosuvastatin on the intestinal flora, lipid metabolism, liver function and inflammation in patients with nonalcoholic fatty liver disease (NAFLD). For this purpose, a total of 96 patients with NAFLD were selected as research subjects and randomly divided into a control group (n=48) and an observation group (n=48). The Control group was treated with rosuvastatin, based on which observation group received Clostridium butyricum capsule treatment. The efficacy in the two groups of patients was compared, and the intestinal flora, lipid metabolism, liver function and inflammation were observed. Results showed that the efficacy in the observation group was significantly better than that in the control group (p<0.05). After treatment, the content of Eubacterium rectale in the observation group was lower than that in the control group, while the content of Bacteroides thetaiotaomicron and Bifidobacteria was notably higher than that in the control group (p<0.05). Moreover, the observation group had remarkably lower levels of total cholesterol (TC), triglyceride (TG), free fatty acids (FFA), total bilirubin (TBIL), direct bilirubin (DBIL), alanine aminotransferase (ALT), aspartate aminotransferase (AST), procollagen III peptide (PIIIP), collagen-IV (C-IV), hyaluronicacid (HA) and laminin (LN) as well as lower levels of tumor necrosis factor-alpha (TNF-α), catabolite activator protein (CAP) and interleukin-6 (IL-6) in serum than the control group (p<0.05). It was concluded that Clostridium butyricum capsules combined with rosuvastatin can effectively improve intestinal flora imbalance, reduce blood lipid levels, and alleviate liver fibrosis and liver function damage in the treatment of NAFLD, so it is of therapeutic value.